A Resident-driven Initiative to Increase Bedside Teaching on Interdisciplinary Rounds. Issue 3 (19th May 2021) - Becker, Andrew; Frosch, Olivia; Argraves, Melissa; Carroll, Bryn; Kamsheh, Alicia; Krass, Polina; Mehta, Sanjiv; Salazar, Elizabeth; Taylor, April; Hart, Jessica
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: Inpatient rounding serves numerous roles. The American Academy of Pediatrics recommends a family-centered bedside model. Residents identified physical examination teaching during and satisfaction with rounds as areas for improvement. A resident group developed a project utilizing quality improvement (QI) methodology to address these concerns. We aimed to increase the frequency of bedside physical examination teaching most or every day on a single inpatient unit by 20% over 1 year, with secondary goals to increase the percentage of interns spending one hour or more at bedside per day by 10% and intern satisfaction by 15%, without impacting rounding duration. Methods: We developed an organizational structure to complete a long-term resident-led project. Interventions included daily bedside examination teaching on rounds, afternoon examinations, goal communication, topic recording, and a teaching "tip sheet." Using an institutional QI framework, we utilized iterative plan-do-study-act cycles to implement interventions and surveys to assess outcomes, with rounding efficiency as a balancing measure. Results: The survey response rate was 57%. Bedside teaching frequency increased from a mean of 10% to 61%, perceived time at the bedside increased from 37% to 59%, and rounding satisfaction improved from a rating of 6.7/10 to 7.4/10. Efficiency was not impacted. Conclusions: We improved inpatient rounds bedside physical examination teaching and satisfaction without sacrificing efficiency. This project demonstrates the feasibility and success of a resident-driven education initiative to successfully motivate fellow residents and colleagues across disciplines to enact change. The organizational structure may serve as a model for resident-led QI projects across institutions.